Network and Evolutionary Analysis Reveals Candidate Genes of Membrane Trafficking Involved in Maize Seed Development and Immune Response - Zheng, Chunyan; Yu, Yin; Deng, Guiling; Li, Hanjie; Li, Faqiang (Frontiers in Plant Science, 2022)
Plant membrane trafficking system plays crucial role in maintaining proper cellular functions and responding to various developmental and environmental cues. Thus far, our knowledge of maize membrane trafficking system is still limited. Here, we systematically identified 479 membrane trafficking genes from maize genome through orthology search and studied their functions by integrating transcriptome and evolution analyses. These genes encode the components of Coated vesicles, AP complexes, autophagy, ESCRTs, Retromers, Rab GTPases, Tethering factors and SNAREs. The maize genes exhibited diverse but coordinated expression patterns, with 249 genes showing elevated expression in reproductive tissues. Further WGCNA analysis revealed that five COPII components and four Rab GTPases had high connectivity with protein biosynthesis during endosperm development, and that eight components of autophagy, ESCRT, Rab and SNARE were strongly co-upregulated with defense related genes and/or with secondary metabolic processes to confer basal resistance to Fusarium graminearum. In addition, we identified 39 membrane trafficking genes with strong selection signals during maize domestication and/or improvement. Among them, ZmSec23a and ZmVPS37A were selected for kernel oil production during improvement and for pathogen resistance during domestication, respectively. In summary, these findings will provide important hints for future appreciation of the functions of membrane trafficking genes in maize.